Learning Strategies at SMP Muhammadiyah 4 Porong During Covid-19 Pandemic - Muhlasin Amrullah; Amellya Nur Syahrani (International Consortium of Education and Culture Research Studies, 2021)
The COVID-19 pandemic has had many impacts on various sectors. One of them is the education sector. Education is also feeling the impact that has occurred due to the COVID-19 pandemic. SMP Muhammadiyah 4 Porong is one of the schools that has felt its impact. Therefore, this research was conducted to find out adaptations, learning strategies, innovations, and efforts faced by schools in implementing distance learning carried out by teachers who teach at SMP Muhammadiyah 4 Porong during the Covid-19 pandemic. This study aims to determine the learning strategies carried out during online learning activities and face-to-face learning activities carried out during the pandemic. This study uses descriptive qualitative research methods, data collection techniques in this study using interviews, observation, and documentation. The results of this study are that there are many challenges faced by SMP Muhammadiyah 4 Porong in carrying out online learning, During the pandemic teaching and learning activities at SMP Muhammadiyah are carried out online, the learning method during online delivery of learning uses internet media such as zoom, google meet, and an application called etmodo. In addition, there are teachers who have less competence in the fields of technology and information in learning, students are undisciplined when conducting online learning, and demands to always have internet quotas that burden students. The solutions include conducting workshops, seminars, and training for teachers related to technology and information used in online learning, as well as carrying out teaching and learning activities that were originally online to face-to-face so that learning is more effective to be carried out while still implementing health and psychological protocol distancing. In this way, it is hoped that teaching and learning activities can run well.